EFFECT OF GOVERNMENT POLICIES ON THE LENDING ABILITY OF DEPOSIT MONEY BANKS IN NIGERIA (Journal of Contemporary Issues in Accounting, 2021)
The study evaluated the effect of government policies on the lending ability of deposit money banks in Nigeria. The study was anchored on the Keynesian theory of monetary policy and the quantitative analysis via the ex-post facto research design was adopted. Data of bank credit to private sector, total domestic debt (proxy for economic growth) and broad money supply were obtained from the Central Bank of Nigeria statistical bulletin and National Bureau of Statistics from 1999-2019. Data obtained was analyzed using the Ordinary Least Square estimation technique. The findings showed that money supply has a significant and positive effect on the lending ability of deposit money banks in Nigeria. In addition, it was found that monetary policy rates have significant and positive effect on the lending ability of deposit money banks in Nigeria. More so, government borrowings have significant and negative effect on the lending ability of deposit money banks in Nigeria. On the basis of the findings, it was recommended among others that the monetary authority in Nigeria should manage the monetary policy rate properly for it to be attractive and affordable for investors to borrow money from the bank. Again, the government should employ other measures such as budgetary control to support and strengthen the monetary policy in order to control the credit creation of deposit money banks in the country.
Keywords: Lending; Money supply; Monetary policy; Government policy; Domestic debt